2022
DOI: 10.52567/pjsr.v4i2.469
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Sectoral Growth in Pakistan

Abstract: Main objective to write this paper was to find out impact of fiscal policy on sectoral growth in Pakistan. Annual data for period 1980-2021 was used from world development indicators of World Bank (2021). ADF and PP unit root test were employed to check the stationarity of all variables. ADRL bound testing was considered as estimation technique because some variables were stationary at level and some were at first difference while no variable was stationary at second difference. Three models were estimated whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While positive sloped Phillips curve or stagflation also stands valid as can be witnessed from the positive coefficient of domestic or consumer prices factor. The positive coefficient of consumer prices is supported by Borhan et al (2023) and Saani et al (2023) while the negative impact of economic growth was endorsed by Aleksandraviciene et al (2023); Ali et al (2021), Ajmair and Bi (2021) and Lima and Marques (2019). Lastly, the positive coefficient of population was validated by Gomez and Irewole (2023) and Irushad et al (2023).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…While positive sloped Phillips curve or stagflation also stands valid as can be witnessed from the positive coefficient of domestic or consumer prices factor. The positive coefficient of consumer prices is supported by Borhan et al (2023) and Saani et al (2023) while the negative impact of economic growth was endorsed by Aleksandraviciene et al (2023); Ali et al (2021), Ajmair and Bi (2021) and Lima and Marques (2019). Lastly, the positive coefficient of population was validated by Gomez and Irewole (2023) and Irushad et al (2023).…”
Section: Resultsmentioning
confidence: 90%
“…In another research, Ali et al (2021) found negative and significant effects of economic growth and inflation on unemployment while they also found positive and significant effects of population on unemployment in the long run in Zanzibar. After Ali et al (2021), the negative and significant effects of GDP on unemployment were disclosed by Ajmair and Bi (2021) for a country like Pakistan. The consumer prices left significantly positive impact on unemployment in model 3 of state 1 while the similar results were witnessed in model 2 of state 2 in case of South African economy [Buthelezi (2023)].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mahtab, Shafiq & Shah 54 ISSN: 2520-0739 Ajmair, Khan, and Bashir (2022) investigate how Pakistan's fiscal strategy has affected sectoral growth. In this research, three models were estimated, with gross domestic product per capita, the entire debt service, commodity and service external balance, and the national GDP serving as independent variables and the dependent variables being agriculture, industry, and services.…”
Section: Literature Reviewmentioning
confidence: 99%